Strategi Edukasi Lingkungan Berbasis Apotek Hidup di SDN 1 Kabar: Membangun Kesadaran Ekologis Sejak Dini - Musabihatul Kudsiah; Mariana Hardianti; Alfiani Nur Izzati; Elawati Elawati; Novia Putri Adekayanti; Dini Parhayana (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2025)
Environmental literacy is a crucial aspect that must be instilled from an early age to shape a generation that cares about environmental sustainability and health. This community engagement program aims to enhance environmental literacy among elementary school students through the implementation of a living pharmacy (apotek hidup) initiative. The activity was conducted at SDN 1 Kabar, East Lombok Regency, involving 48 students from grades IV and V as participants. A participatory approach was employed, emphasizing hands-on practice through stages of education, planting, and maintaining medicinal plants within the school environment. The evaluation results showed significant improvements in three indicators of environmental literacy. Knowledge of medicinal plants increased from 46% in the pretest to 82% in the posttest; skills in planting and plant care rose from 40% to 75%; and environmental awareness improved from 50% to 68%. This program not only provided contextual, experience-based learning but also fostered early ecological and health awareness. The living pharmacy proved to be an effective, engaging, and relevant educational medium for developing environmental literacy in elementary schools.